1992
DOI: 10.1161/01.hyp.19.6.555
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive, episodic hypoxia causes diurnal elevation of blood pressure in rats.

Abstract: An association between chronic high blood pressure and obstructive sleep apnea has been described. We hypothesized that repetitive episodic hypoxia patterned after the hypoxia seen in sleep apnea could contribute to diurnal elevation of blood pressure. Using 12-second infusions of nitrogen into daytime sleeping chambers, four groups of male rats (250-375 g) were subjected to intermittent hypoxia (3-5% nadir ambient oxygen) every 30 seconds, 7 hours per day for up to 35 days. In one group, blood pressure was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
311
3
19

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(361 citation statements)
references
References 29 publications
21
311
3
19
Order By: Relevance
“…However, there may be shortcomings that limit or constrain the potential of CIH as a therapeutic tool. For example, certain CIH protocols elicit pathophysiology such as systemic hypertension (Fletcher et al, 1992), altered sympathetic chemoreflexes (Greenberg et al, 1999), and hippocampal apoptosis (Gozal et al, 2001). These pathophysiological effects probably depend on the duration and severity of hypoxia.…”
Section: Significancementioning
confidence: 99%
“…However, there may be shortcomings that limit or constrain the potential of CIH as a therapeutic tool. For example, certain CIH protocols elicit pathophysiology such as systemic hypertension (Fletcher et al, 1992), altered sympathetic chemoreflexes (Greenberg et al, 1999), and hippocampal apoptosis (Gozal et al, 2001). These pathophysiological effects probably depend on the duration and severity of hypoxia.…”
Section: Significancementioning
confidence: 99%
“…Patients with recurrent apneas are at risk for developing several comorbidities including hypertension, sympathetic activation, breathing abnormalities, atherosclerosis, and stroke (4)(5)(6)(7)(8). Exposure of rodents to IH alone induces several co-morbidities reported in patients with recurrent apnea (9)(10)(11). However, little information is available on the molecular mechanisms underlying the morbidities associated with IH.…”
mentioning
confidence: 99%
“…2,3 CIH of OSA has been associated with an increased risk of hypertension, type 2 diabetes, dyslipidemia, and atherosclerosis, independent of underlying obesity. 2,[4][5][6][7][8][9] Moreover, studies in rodent models of intermittent hypoxia (IH) demonstrated that CIH can cause hypertension, 10 insulin resistance, 11 and dyslipidemia. 12,13 Thus, CIH of OSA has been implicated in causality of cardiovascular and metabolic disorders, independent of obesity.…”
mentioning
confidence: 99%